Acute Pancreatitis: An Unusual Side Effect of Adalimumab in Crohn’s Disease Patient - Walid El Ouardi; Mustapha Benazzouz (Clinical Medicine Insights: Case Reports)
Background: Drug-induced acute pancreatitis is a rare condition occurs at an incidence rate of 0.1–1.4% and represents a diagnostic challenge. TNFα inhibitors specially adalimumab is very rarely reported in the literature, primarily through case reports, as a potential cause of acute pancreatitis. Case presentation: Our case report presents a case of a 23-year-old patient followed for Crohn disease in whom a diagnosis of acute pancreatitis induced by adalimumab was made. This diagnosis was confirmed after the elimination of other possible etiologies, and notably by the recurrence of pancreatitis after Adalimumab rechallenge. The occurrence of acute pancreatitis induced by TNFα inhibitors exposes to the risk of pancreatitis with other drugs in this class, hence the need to switch to another therapeutic class, which was Ustekinumab in our case. Conclusion: Acute pancreatitis is an unusual complication of treatment with Adalimumab. Through our experience, based on solid scientific data, we want to draw the attention of clinicians to the reality of this complication. It should be considered in any patient on TNFα inhibitors who presents with acute pancreatitis without an obvious cause.